2020
DOI: 10.34133/2020/2872141
|View full text |Cite
|
Sign up to set email alerts
|

Common-Ion Effect Triggered Highly Sustained Seawater Electrolysis with Additional NaCl Production

Abstract: Developing efficient seawater-electrolysis system for mass production of hydrogen is highly desirable due to the abundance of seawater. However, continuous electrolysis with seawater feeding boosts the concentration of sodium chloride in the electrolyzer, leading to severe electrode corrosion and chlorine evolution. Herein, the common-ion effect was utilized into the electrolyzer to depress the solubility of NaCl. Specifically, utilization of 6 M NaOH halved the solubility of NaCl in the electrolyte, affording… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 35 publications
(38 reference statements)
0
31
0
Order By: Relevance
“…Therefore, chloride oxidation and corrosion issues becomes increasingly severe. In a very recent report, seawater electrolysis in saturated NaCl was performed at 500 mA cm À2 for more than 100 h in 6 M NaOH when commonion effects were introduced with an LDH derived phosphide as a bifunctional electrode, 218 which led to stable triple production of H 2 , O 2 and NaCl. Therefore, after the selectivity and corrosion issues mentioned above have been solved, we believe LDHs, and their derivatives, can be employed in alkaline electrolysers for seawater splitting in real applications after adopting appropriate engineering designs such as anti-corrosion electrolyte storage systems, NaCl crystallization units, etc.…”
Section: Feasibility Of Using Ldhs As Oer Catalysts For Seawater Splittingmentioning
confidence: 99%
“…Therefore, chloride oxidation and corrosion issues becomes increasingly severe. In a very recent report, seawater electrolysis in saturated NaCl was performed at 500 mA cm À2 for more than 100 h in 6 M NaOH when commonion effects were introduced with an LDH derived phosphide as a bifunctional electrode, 218 which led to stable triple production of H 2 , O 2 and NaCl. Therefore, after the selectivity and corrosion issues mentioned above have been solved, we believe LDHs, and their derivatives, can be employed in alkaline electrolysers for seawater splitting in real applications after adopting appropriate engineering designs such as anti-corrosion electrolyte storage systems, NaCl crystallization units, etc.…”
Section: Feasibility Of Using Ldhs As Oer Catalysts For Seawater Splittingmentioning
confidence: 99%
“…In addition, optimization of the external conditions, such as temperature, pH, and concentration of Cl − , could also alleviate both chlorine corrosion and competitive reactions simultaneously. Sun and co-workers 87 employed NiCoFe phosphide as a bifunctional electrode in a simulative seawaterelectrolysis system. This electrode afforded a current density of 500 mA•cm −2 for over 100 h, the Faradaic efficiency of which was approximately 100%.…”
Section: In Situ Generated Resistive Speciesmentioning
confidence: 99%
“…by the formation of soluble species at both cathode and anode [ 21 , 22 , 23 ]. NaCl being the main constituent (average content of 35 g per L), the roadmap is to test the possible electrocatalysts using seawater-based electrolyte, which consists of running the experiments in the absence and presence of NaCl (0 to 3 M) [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ], similar to studies in corrosion science [ 35 ]. Vos et al [ 28 ] have examined the likely competition between the oxygen evolution reaction (OER) and the chlorine evolution reaction at the anode (CER, Equation (1)), which is known as the chloride ions oxidation (ClOR, Equation (2)).…”
Section: Introductionmentioning
confidence: 99%
“…Recent results show that the alkaline medium (the most envisaged media [ 36 , 37 ]) produces the best selectivity at Ni-based electrocatalysts (200 mA cm −2 and 1.6 V for 100 h) [ 23 , 25 , 26 , 27 , 38 ]. Amikam et al [ 39 ] found that ClOR in NaCl-saturated solutions is inhibited at [NaOH] ≥ 2.5 M. This is particularly interesting for real electrolysis conditions where NaCl may accumulate in the electrolyte if seawater is continuously fed to the system and H 2 O is converted to H 2 and O 2 [ 31 , 32 ]. Less research is dedicated to that while the continuous neutral seawater electrolysis can also likely trigger the chloride ions accumulating progressively to accelerate the corrosion processes and/or to favor undesirable chloride oxidation (ClOR) to chlorine/hypochlorite [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation